2013
DOI: 10.1111/bcpt.12178
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products Evaluated in Neuropathic Pain Models ‐ A Systematic Review

Abstract: Chronic pain conditions, such as neuropathic pain, are a common problem that poses a major challenge to health-care providers due to its complex natural history, unclear aetiology and poor response towards therapy. Despite the large number of drugs available, the adherence is limited by the large range of side effects and pharmacological ineffectiveness. Thus, the search for new chemical entities that can act as promising molecules to treat chronic pain conditions has emerged. The natural products remain as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 93 publications
(81 reference statements)
1
48
0
1
Order By: Relevance
“…In a review of 174 published trials, Finnerup et al (2010) reported that no available drug treatments are able to relieve all neuropathic pain conditions [25]. Therefore, therapeutic treatment of neuropathic syndromes remain challenging on account of their complex natural history, unclear etiology, and poor response to drugs [26]. The anti-epileptic drug gabapentin is widely used to treat neuropathic pain, and it effectively relieves allodynia, burning pain, shooting pain, and hyperesthesia [27].…”
Section: Introductionmentioning
confidence: 99%
“…In a review of 174 published trials, Finnerup et al (2010) reported that no available drug treatments are able to relieve all neuropathic pain conditions [25]. Therefore, therapeutic treatment of neuropathic syndromes remain challenging on account of their complex natural history, unclear etiology, and poor response to drugs [26]. The anti-epileptic drug gabapentin is widely used to treat neuropathic pain, and it effectively relieves allodynia, burning pain, shooting pain, and hyperesthesia [27].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, we cannot isolate these terpenoids in EOX to test them separately. Even so, it is possible that the pharmacological properties, such as anti-inflammatory and analgesic, of EOX are related to the presence of terpenoid compounds [5254]. …”
Section: Discussionmentioning
confidence: 99%
“…Monoterpenes are commonly able to produce analgesic, antioxidant and antiinflammatory effects, including their ability to treat chronic pain (Guimaraes, Quintans & Quintans Júnior, 2013;Guimaraes, Serafini & Quintans-Junior, 2014;Quintans, Antoniolli, Almeida, Santana-Filho & Quintans-Junior, 2014). These compounds possess a poor oral absorption due to their extremely low aqueous solubility or their extensive pre-systemic metabolism and this may be responsible for the unfavorable pharmacokinetics of the molecule (Yadav, Suresh, Devi & Yadav, 2009).…”
Section: Pharmacological Improvementmentioning
confidence: 99%